Intelligent cyber-physical systems security for industry 4.0 : applications, challenges and management - Banerjee, Jyoti Sekhar; Bhattacharyya, Siddhartha, 1975-; Obaid, Ahmed J. (Ahmed Jabbar); Ye, Weichang (Boca Raton, FL : CRC Press, 2022)
"Intelligent Cyber-Physical Systems Security for Industry 4.0: Applications, Challenges and Management presents new cyber-physical security findings for Industry 4.0 using emerging technologies like Artificial Intelligence (with Machine / Deep Learning), Data Mining, Applied Mathematics. All these are the essential components for processing data, recognizing patterns, modelling new techniques, and improving the advantages of the Data Science more"--
OCLC-licensed vendor bibliographic record.
Keywords: Cooperating objects (Computer systems); Industry 4.0.; COMPUTERS / Artificial Intelligence; COMPUTERS / Database Management / Data Mining